2015
DOI: 10.1007/s11665-015-1785-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Cr-SiC Particles-Reinforced Fe-Based Alloy Coating

Abstract: In this study, SiC particles were first coated with Cr to form a layer that can protect the SiC particles from dissolution in the molten pool. Then, the Cr-SiC powder was injected into the tail of molten pool during plasma-transferred arc welding process (PTAW), where the temperature was relatively low, to prepare CrSiC particles reinforced Fe-based alloy coating. The microstructure and phase composition of the powder and surface coatings were analyzed, and the element distribution and hardness at the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is speculated that the performance of iron-based coatings in erosive and harsh environment service conditions, such as marine pumps, could also be improved with the addition of some hard materials to the steel powder matrix, such as carbides, nitrides, and borides [1,2,26,27]. Fe 3 C and SiC have been considered as the reinforcement phases in this study due to their high hardness, good wear resistance, and low cost, especially compared to borides and nitrides [28,29]. However, limited research has been conducted on the iron-based composite coatings with hard particle reinforcements [22,29], and, particularly, there is a lack of information about characteristics of such steel coatings produced using thermal-spraying technology.…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that the performance of iron-based coatings in erosive and harsh environment service conditions, such as marine pumps, could also be improved with the addition of some hard materials to the steel powder matrix, such as carbides, nitrides, and borides [1,2,26,27]. Fe 3 C and SiC have been considered as the reinforcement phases in this study due to their high hardness, good wear resistance, and low cost, especially compared to borides and nitrides [28,29]. However, limited research has been conducted on the iron-based composite coatings with hard particle reinforcements [22,29], and, particularly, there is a lack of information about characteristics of such steel coatings produced using thermal-spraying technology.…”
Section: Introductionmentioning
confidence: 99%
“…Although SiC had been reported to be used as a reinforcement, correspondingly, in welding layers prepared using LCM [7,14], the effect of the co-addition of SiC and CeO 2 on the microstructure and wet wear of Fe-based welding layers has rarely been investigated. In this study, we focus on investigating the influence of microstructures by SiC and CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The bending strength, impact strength and hardness is 15.9%, 27.8% and 4.7% higher, when compared to uncoated composites, respectively, and the wear mass loss is half of that for uncoated composites. Wang et al [23] used powder embedding reaction coating technology to form a Cr coating layer on the SiC surface, and deposited Crcoated SiC particles on the carbon steel substrate using plasma surfacing technology. The results indicated that the interface reaction led to chemical composition changes between the reinforcements and matrix, and that SiC chemically bonded with the carbon steel substrate.…”
Section: Introductionmentioning
confidence: 99%